The influence of the decoy effect on price and location on consumer purchasing decisions at Starbucks Coffee Merr Surabaya - Nurkhalishah, Tiara Dita; Winarno, Sri Tjondro; Rizkiyah, Noor (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2024)
The increasing number of coffee shops in the East Surabaya area, particularly Merr Street or Ir. H. Soekarno Street has created intense competition and a dynamic market environment. This study aims to analyze the impact of Price (X1) and Location (X2) on Purchasing Decisions (Y), moderated by the Decoy Effect (Z), among Starbucks Merr coffee consumers in Surabaya City. The research utilizes Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with WarpPLS 7.0 software. Data was gathered through a questionnaire distributed to 100 respondents using a non-probability sampling technique, specifically accidental sampling. This study demonstrates that price and location significantly affect purchasing decisions at Starbucks Merr. Price accounts for a 30.4% impact, influenced by affordability and frequent promotions, while location has a more substantial effect, with a 56% influence due to its accessibility and strategic positioning. The decoy effect negatively moderates the price-to-purchase relationship, making consumers more inclined to select higher-priced products. However, the decoy effect does not significantly impact the location-purchase relationship, as consumers prioritize convenience and service quality over pricing strategies. These findings underscore the vital role of both pricing and location in Starbucks Merr's marketing strategy.